2018
DOI: 10.1038/s41598-018-27671-z
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling of water and alkali soluble cottonseed protein isolates

Abstract: Currently, there is only limited knowledge on the protein types and structures of the cottonseed proteins. In this work, water-soluble cottonseed proteins (CSPw) and alkali-soluble cottonseed proteins (CSPa) were sequentially extracted from defatted cottonseed meal. Proteins of the two fractions were separated by 4–20% gradient polyacrylamide gel electrophoresis (SDS-PAGE); There were 7 and 12 polypeptide bands on SDS-PAGE of CSPa and CSPw, respectively. These individual bands were then excised from the gel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
3
20
1
Order By: Relevance
“…Sin a 1 has been shown to be related to B. rapa and B. napus napins at the sequence level ( Rahman et al, 2020 ). The database search also showed that rapeseed cruciferins ( Supplementary Table 1 ) have high similarity with rice glutelins which have been reported as antimicrobial peptides ( Bundó et al, 2014 ), as well as the antibacterial glycinin protein from G. max ( Sitohy et al, 2012 ; Yang et al, 2016 ) and antibacterial Legumin A (P09802) from Gossypium hirsutum L. ( Supplementary Figure 1B ) ( He et al, 2018 ). These results suggested the napin and cruciferin are most likely to have antimicrobial properties as well.…”
Section: Discussionmentioning
confidence: 94%
“…Sin a 1 has been shown to be related to B. rapa and B. napus napins at the sequence level ( Rahman et al, 2020 ). The database search also showed that rapeseed cruciferins ( Supplementary Table 1 ) have high similarity with rice glutelins which have been reported as antimicrobial peptides ( Bundó et al, 2014 ), as well as the antibacterial glycinin protein from G. max ( Sitohy et al, 2012 ; Yang et al, 2016 ) and antibacterial Legumin A (P09802) from Gossypium hirsutum L. ( Supplementary Figure 1B ) ( He et al, 2018 ). These results suggested the napin and cruciferin are most likely to have antimicrobial properties as well.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, recent protein characterization studies on Gossypium species have reported 60~70% of the total seed proteins belonging to vicilin and legumin families; the later contributed more. These workers have also shown more heterogeneity in the molecular weights of the legumin A subunits (30 kDa, 17~20 kDa and 11~12 kDa) and less in legumin B subunits (11~13 kDa) (Hu et al 2011;He et al 2018). Further analysis indicated the polypeptide of molecular weight 58 kDa as a precursor of legumin A subunits.…”
Section: Discussionmentioning
confidence: 95%
“…vicilin and legumin accounting for 60~70% of cotton seed proteins (Hu et al 2011). A recent study on water-and alkali-soluble cottonseed proteins (He et al 2018) in G. hirsutum exhibited the presence of 6 and 12 major protein bands on SDS-PAGE belonging to CSPa and CSPw, respectively. Among these proteins, the most abundant peptides were shown to be legumin and vicilin types.…”
Section: Introductionmentioning
confidence: 98%
“…There are also known derivatives of vicilins: a vicilin-like glycoprotein from Nicotiana sylvestris 46 and a low molecular weight vicilin-like glycoprotein from Citrullus lanatus seeds 47 . He and collaborators 48 revealed the presence of vicilin GC72-A in the cotton seed extract - a plant belonging to the Malvaceae family. The same protein was detected in the high molecular weight fraction analysed in our experiments.…”
Section: Discussionmentioning
confidence: 99%